PEMASARAN BERKELANJUTAN : ANALISIS STRATEGI PT UNILEVER DALAM MEMPRODUKSIKAN PRODUK RAMAH LINGKUNGAN - Juanita, Rekha; Sumardi, Rizqi Angelika; Saleh, Mohamad Zein (Jurnal Manajemen, 2024)
This research investigates the impact of sustainable marketing strategies implemented by PT Unilever on consumer acceptance of environmentally friendly products. PT Unilever, as a leading multinational company, has taken a serious commitment to producing products that prioritize environmental sustainability. The study explores how Unilever's marketing strategies have influenced consumer awareness of sustainable products, whether consumers are more likely to choose Unilever's sustainable products, and other impacts on the company's image and business sustainability. The results of this research provide a better scientific understanding of how companies can achieve success in marketing sustainable products and contribute to positive changes in consumer behavior.